Navigating Through Caries Excavation and Pulp Capping Techniques in Permanent Teeth - Karanjot Gill; Richard G. Stevenson, III (Elsevier, 2024)
Dental caries is a prevalent oral health issue and requires appropriate intervention to mitigate its progression and consequent effects. In recent times, dental research has witnessed remarkable advancements that have revolutionized the way we approach caries removal. By examining the recent literature, we aim to provide a clinical guide for safe caries removal and pulp capping techniques while preserving sound tooth structure and preventing iatrogenic damage.